PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN GEOGEBRA CLASSROOM TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 IV KOTO AUR MALINTANG KABUPATEN PADANG PARIAMAN - Putriardi Pratama, Lara; Aima, Zulfitri; Mardiyah, Ainil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low ability of SMPN 1 IV Koto Aur Malintang students to understand mathematical concepts. These students struggle to solve practical exercises that deviate from the examples provided by the teacher and their low active engagement during learning. This affects the students' low learning performance and does not meet the KKTP defined by the school. This study aims to determine the effect of the Project-Based Learning (PjBL) model supported by the Geogebra class on the understanding of mathematical concepts of 8th grade students of SMPN 1 IV Koto Aur Malintang. This study uses a true post-test experimental design with a single control group. The research sample consists of Grade VIII.1 as the control group and Grade VIII.2 as the experimental class. The instrument used in this study is a post-test in the form of essay questions with a reliability of 0.895. The post-test data analysis shows that the data from the experimental class are not normally distributed. Therefore, the Mann-Whitney test was continued using Minitab version 19, with a p-value of 0.145 at a significance level of . Since the p-value > , is accepted and , is rejected. From the results of this study, it can be concluded that students’ understanding of mathematical concepts when applying the project-based learning model of Geogebra Classroom is not better than their understanding of mathematical concepts when applying the conventional learning model in class VIII SMPN 1 IV Koto Aur Malintang.